2021
DOI: 10.3390/s21165345
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Weak C-Axis Preferred AlN Thin Film for Temperature Measurement

Abstract: A weak C-axis preferred AlN thin film with a lot of defects was fabricated for temperature measurement. It was found that the (002) diffraction peak of the thin film increased monotonously with the increase in annealing temperature and annealing time. This phenomenon is ascribed to the evolution of defects in the lattice of the AlN film. Therefore, the relationship between defects and annealing can be expressed by the offset of (002) diffraction peak, which can be used for temperature measurement. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Many groups have used different annealing treatments with different temperatures and times to change the film structure and improve performance. Then, the changes in chemical composition and crystallinity for AlN films before and after annealing were studied [9][10][11]. In this work, we show our advancements towards low-loss high-confinement sputter deposited AlN waveguides for PICs.…”
Section: Introductionmentioning
confidence: 91%
“…Many groups have used different annealing treatments with different temperatures and times to change the film structure and improve performance. Then, the changes in chemical composition and crystallinity for AlN films before and after annealing were studied [9][10][11]. In this work, we show our advancements towards low-loss high-confinement sputter deposited AlN waveguides for PICs.…”
Section: Introductionmentioning
confidence: 91%
“…For temperature measurement, Dong et al [ 20 ] produced a weak thin AlN layer with numerous defects. It was found that the thin film diffraction peak (002) increased monotonously with an increasing annealing temperature and an annealing time.…”
Section: Introductionmentioning
confidence: 99%
“…The methods of measuring the surface temperature of turbine blades mainly include thin-film thermocouples [ 21 , 22 , 23 ], temperature indicating paint [ 24 ], infrared radiation [ 25 , 26 , 27 ], and irradiation crystals [ 28 , 29 , 30 ]. Based on the advantages of irradiating crystals, the authors [ 20 ] proposed an easy and cheap method of temperature measurement using a thin-film crystal. It was noted that the crystal quality could be strengthened after annealing [ 31 , 32 , 33 ], indicating that the AlN thin layer is a promising material for temperature measurement.…”
Section: Introductionmentioning
confidence: 99%